Is Household Composition Associated With Repeat Fight Injuries in Adolescents Living in Urban Neighborhoods? - Ryan, Leticia Manning (Journal of interpersonal violence, 2021)
The association of household composition with violence-related injury risk has not been explored in the at-risk urban adolescent population. We hypothesize that, similar to the unintentional risk association, higher adult:child ratio, lower household size, and the presence of a grandparent are protective and thus associated with lower risk for repeat fight injury in this population. This is a cross-sectional study of 10- to 15-year-old adolescents who were evaluated in two urban, pediatric emergency departments (EDs; Baltimore, MD, Philadelphia, PA) for a peer fight-related injury between June 2014 and June 2016. Logistic regression was used to test for associations between each household composition measure of interest and youth self-report of a medically attended fight-related injury within the prior 12 months. Of 187 eligible youth, 62 (33%) reported at least one such repeat fight-related injury. With control for potential confounders, youth with past fight injuries did not differ in adult:child ratio (adjusted odds ratio [adj OR] = 1.3, 95% confidence interval [CI]: [0.9, 1.9] ) or household size (adj OR = 0.9, 95% CI: [0.8, 1.1]) but were more likely to have a grandparent residing in the household (adj OR = 3.3, 95% CI: [1.4, 7.9]). Our data demonstrate a positive association between presence of a grandparent in the household and risk for repeat fight injury in urban adolescents without a corresponding association with adult:child ratio or total household size. Further study should explore differences among the households of urban adolescents with and without grandparent presence to further understand this association and define the mechanisms that may contribute to these findings.